Enhanced photovoltaic effect of polycrystalline BiFeO3 film. Issue 4 (11th January 2013) - Liu, Baoting; Peng, Zengwei; Ma, Jikui; Wang, Jinfeng; Zhao, Qingxun; Wang, Yinglong
Abstract Polycrystalline BiFeO3 (BFO) film has been fabricated on Pt(111)/Ti/SiO2/Si(001) substrate by a magnetron sputtering method. Both red light of 632.8 nm and purple light of 404 nm have been used to irradiate the sample. It is found that illumination of the sample by the two kinds of lights can induce an increase of the leakage‐current density. The increase of current density by purple light is about two orders of magnitude larger than that without irradiation, while an increase of an order of magnitude is produced by red light. Moreover, an enhanced photovoltaic effect has been observed when the sample is illuminated by purple light. The photocurrent at zero bias increases from 0.08 µA cm−2 in the dark to 3.2 µA cm−2 in purple light. The open‐circuit voltage is 0.28 V.